2018
DOI: 10.1111/echo.13853
|View full text |Cite
|
Sign up to set email alerts
|

Early modifications of cardiac function in preterm neonates using speckle tracking echocardiography

Abstract: Echocardiographic assessment of myocardial deformation parameters is feasible in preterm infants. Our data suggest that the maturational process of the myocardium is due to the development of the epicardial layer after birth, which allows the acquisition of the twist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…The higher indices of twist and torsion seen in the premature population are due to the change in basal rotation from an anticlockwise to clockwise motion. This was also reported in preterm infants by Castaldi et al 21 This concept is further reinforced with the strong positive correlation between LV torsion and untwist rate in the entire cohort during the third scan in this study. The adaptive response of LV twist in our premature cohort most likely evolved due to diminished longitudinal function and not consequent to any interplay with pulmonary haemodynamics, since the relative indices of PVR were equivalent between preterm and term babies.…”
Section: Summary Of Findingssupporting
confidence: 91%
“…The higher indices of twist and torsion seen in the premature population are due to the change in basal rotation from an anticlockwise to clockwise motion. This was also reported in preterm infants by Castaldi et al 21 This concept is further reinforced with the strong positive correlation between LV torsion and untwist rate in the entire cohort during the third scan in this study. The adaptive response of LV twist in our premature cohort most likely evolved due to diminished longitudinal function and not consequent to any interplay with pulmonary haemodynamics, since the relative indices of PVR were equivalent between preterm and term babies.…”
Section: Summary Of Findingssupporting
confidence: 91%
“…Recent echocardiographic, magnetic resonance and CT imaging studies indicate that preterm infants have larger left atria and lower diastolic function than term infants (14)(15)(16)(17), suggesting that the heart failure among young adults who were born preterm has developmental origins. Serum from preterm infants was shown to have higher levels of malonyl-carnitine and lower levels of palmatoylcarnitine than serum from term infants born (62), suggesting a link between preterm birth and reduced FASN activity.…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies have reported a loss of pulmonary capillaries, altered ventricular shape and decreased aortic size in young adults born preterm (9)(10)(11)(12)(13), the root causes of pulmonary hypertension, heart failure and other cardiovascular diseases in the survivors of preterm birth remain poorly understood. Recent echocardiographic, magnetic resonance, and CT imaging studies indicate that preterm infants have larger left atria and lower diastolic function than term infants (14)(15)(16)(17). These changes may be an early and direct response to oxygen exposure because diastolic heart failure has been seen in preterm infants on supplemental oxygen therapies (18).…”
Section: Introductionmentioning
confidence: 99%
“…While prior studies have reported a loss of pulmonary capillaries, altered ventricular shape, and decreased aortic size in young adults born preterm (9)(10)(11)(12)(13), the root causes of pulmonary hypertension, heart failure, and other cardiovascular diseases in the survivors of preterm birth remain poorly understood. Recent echocardiographic imaging, MRI, and CT imaging studies indicate that preterm infants have larger left atria and lower diastolic function than term infants (14)(15)(16)(17). These changes may be an early and direct response to oxygen exposure because diastolic heart failure has been seen in preterm infants on supplemental oxygen therapies (18).…”
Section: Introductionmentioning
confidence: 99%